Pengaruh Pendekatan Matematika Realistik (PMR) Terhadap Kemampuan Berpikir Kreatif Kelas IV SDN Sunter Agung 03 Pagi Jakarta Utara - Wahyu Oktavianingsih; Pramudiani, Puri (Universitas Pendidikan Ganesha, 2022)
Creative thingking ability is one of the important abilities possessed by students. However, the facts on the ground show that students' creative thinking skills are still low. One of the causes of these problems is the use of less innovative learning approaches. This study aims to analyze the effect of realistic mathematics approach on the creative thinking ability of fourth grade elementary school students. This type of research is a quasi experiment using the Randomize Control Group Post Test Only design. The population of this study amounted to 74 people. The sample of this study was 52 people who were determined using the Randome Sampling technique. Data was collected using an instrument in the form of a creative thinking ability test. Data were analyzed quantitatively by using t-test. The results showed that there was a significant difference between students' creative thinking abilities in the experimental class and the control class. This is indicated by the t-value of 2.537 and p-values ​​of 0.014 (<0.05). Based on these results, it can be concluded that the realistic mathematics approach has an influence on the creative thinking skills of fourth grade elementary school students.